Legality for Electronic Signatures in Implementing Electronic Medical Records - I Wayan Dody Putra Wardana; Ni Ketut Supasti Dharmawan; Ni Luh Gede Astariyani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
An electronic signature is an authentic marker to show a person's responsibility. Electronic signatures also ensure confidentiality, integrity, authorization, access control, and non-repudiation of information in electronic medical records. Therefore, this research was conducted to determine the legal aspects of electronic signatures in administering electronic medical records. This research used a qualitative method with a normative juridical approach. The research sources were based on laws, government regulations, journals, and other tertiary sources related to electronic signatures and electronic medical records in health facilities. Research findings illustrated that Minister of Health Regulation Number 24 of 2022 concerning medical records only defined electronic signatures as an authentication and verification of the security and privacy of medical record information. Electronic signatures are specifically regulated by Constitution Number 11 of 2008 concerning Information and Electronic Transactions and Government Regulation Number 71 of 2019 concerning Electronic Systems and Transaction Operators. Both certified and uncertified electronic signatures have legal legitimacy in their application in electronic medical records. However, how they are supported by evidence is what makes them different. Certified electronic signatures are more trustworthy than uncertified electronic signatures.